Improved accuracy for FASTSIM using one or three flexibility values. Issue 1 (2nd January 2023) - Vollebregt, Edwin; Voltr, Petr
Abstract : This paper presents a correction and an extension of the FASTSIM approach for the computation of the wheel–rail creep forces. The correction concerns the variants of FASTSIM using a single flexibility value. Kalker's formula for this gives up to 41 % too large flexibility in situations with mixed creepage, underestimating the creep forces by 29 % . This is corrected using new approaches for the flexibilities' combination. The extension concerns the variants of FASTSIM using three flexibility values. These variants misrepresent the creep force direction at large creepage. This is resolved using a blending approach, that roughly halves the errors of FASTSIM compared to CONTACT.